Genotyping of hepatitis B virus by restriction enzyme analysis - Aksoy, Aziz; Özdarendeli, Aykut (My University, 2006)
Hepatitis B is one of the most common infectious diseases in the world, and 350 million people have been estimated to be chronic hepatitis B virus carriers world-wide. Hepatitis B virus (HBV) has been classified into 8 genotypes (A-H) based on an intergroup divergence of 8% or more in the complete nucleotide sequence. Different genotypes of the hepatitis B virus may influence the clinical outcome of the disease. HBV genotyping method using restriction fragment length polymorphism (RFLP) can reliably identify genotypes. HBV genotyping with S gene sequence is consistent with genetic analysis using the full genomic sequences. The aim of this study was to determine the genotypes of HBV by using restriction fragment length polymorphism (RFLP) method in the region of Elazig. A total of 127 HBV-DNA positive patients (74 male, 53 female) were included in the study. Semi-nested polymerase chain reaction (PCR) was performed to amplify the specific parts of HBV S gene. In the first step, 685 base paired (bp) region was amplified by sense primer HBMF-1 and anti-sense primer HBMR2, while in the second step 485 bp region was amplified by using inner-sense primer HBMF2 and anti-sense primer HBMR2. PCR products were then digested by the restriction enzymes, Alwl, Earl, Hphl, Ncil and NlalV. The RFLP assay indicated that genotype D was the only detected type in our samples. In conclusion, genotype D is the predominant type among hepatitis B patients in our region. RFLP is considered to be an easy and useful method for genotyping HBV strains.
Hepatit B virusunun restriksiyon enzim analizi ile tiplendirilmesi
Keywords: HBV genotyping; Hepatitis B virus; PCR; RFLP